2020
DOI: 10.1101/2020.06.12.148254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BUB-1 targets PP2A:B56 to regulate chromosome congression during meiosis I inC. elegansoocytes

Abstract: During cell division, a balance between protein kinases and phosphatases is required to achieve specific and highly regulated phosphorylation levels. Protein Phosphatase 2A (PP2A) is a heterotrimeric enzyme composed of Scaffold (A), Catalytic (C), and Regulatory (B) subunits. PP2A can be targeted to different locations by specific interactions with one of several possible B subunits. B56-type subunits play important roles during meiosis in yeast and mice, including the protection of centromeric cohesion (targe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…KNL-1, BUB-1, CLS-2, and other cell division proteins have been described previously as being present in roughly linear cortical structures that also are present throughout the assembling oocyte meiotic spindle. These structures previously have been referred to both as rods and as linear elements (17)(18)(19)(20), and one component can indeed form linear filaments in vitro and greatly extended linear structures when overexpressed in vivo (33). Here we refer to these cortical structures as patches, given their less linear appearance as meiosis I proceeds, and to distinguish them from the more linear spindle-associated elements.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…KNL-1, BUB-1, CLS-2, and other cell division proteins have been described previously as being present in roughly linear cortical structures that also are present throughout the assembling oocyte meiotic spindle. These structures previously have been referred to both as rods and as linear elements (17)(18)(19)(20), and one component can indeed form linear filaments in vitro and greatly extended linear structures when overexpressed in vivo (33). Here we refer to these cortical structures as patches, given their less linear appearance as meiosis I proceeds, and to distinguish them from the more linear spindle-associated elements.…”
Section: Discussionmentioning
confidence: 97%
“…During oocyte meiotic cell division, CLS-2 localizes to spindle microtubules, to kinetochores, and to small patches, also called linear elements or rods, distributed throughout the assembling spindle and the oocyte cortex (Monen et al 2005; Dumont, Oegema, and Desai 2010; Bel Borja et al 2020). We previously reported two prominent defects during meiosis I cell division in mutant oocytes produced by worms homozygous for null mutations in the cls-2 locus (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in C. elegans, BUB1-bound PLK1 phosphorylates the BUB1 ABBA motif to both enhance CDC20 binding and promote CDC20 dephosphorylation/activation, which together helps to activate the APC/C and allow timely mitotic exit (Houston et al, 2023). C. elegans BUB1 contains similar PLK1-and PP2Abinding motifs to BUBR1, and these are important for chromosome alignment and segregation during meiosis I (Bel Borja et al, 2020;Taylor et al, 2023). Cross-talk between PLK1 and PP2A has not been evaluated in worms, but it is notable that a PLK1 phosphorylation site is preserved in the PP2A-B56-binding site.…”
Section: Negative Feedbackmentioning
confidence: 99%
“…A recent study found that PP2A is necessary for female meiotic progression, such as spindle assembly and chromosome segregation. The mechanism is that BUB-1 targets PP2A-B′56 via a conserved LxxIxE motif and this regulation is necessary for correct meiotic progression ( Bel Borja et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%